Occurrence of Cryptosporidium in Anglonubian goats in the municipality of Teresina, state of Piauí, Brazil - de Oliveira, Marcelo Richelly Alves; Luz, Carlos Syllas Monteiro; Evangelista, Amauri Felipe; Castro, Geandro Carvalho; Bresciani, Kátia Denise Saraiva [UNESP]; dos Santos, Karina Rodrigues; de Sousa Júnior, Severino Cavalcante (My University, 2023)
This research aimed to investigate the occurrence of Cryptosporidium and correlate it with types of housing, feces consistency, and physiological parameters related to the reproductive status of Anglo-Nubian goats reared in the State of Piauí, Brazil. A total of 180 fecal samples were collected from 60 non-pregnant and lactating goats with a mean weight of 35 kg, a body condition score of 3.5, and a mean age of three years from an experimental herd at the Federal University of Piauí (UFPI). Oocysts of protozoa of the genus Cryptosporidium could be found in the studied animals using the modified Ziehl-Neelsen technique in fecal smears and the image analysis system to perform morphometry. Each independent variable in the quantitative and qualitative analyses, that is, weight, body condition score (BCS), physiological status (non-pregnant or lactating), feces consistency (normal, pasty, or diarrheal), and floor types (concrete and slatted), was tested with the dependent variable (positive samples, i.e., the presence of Cryptosporidium oocysts). Twenty-four out of the total number of fecal samples were considered positive for the presence of the protozoan, which means that 13.3% of the animals were parasitized. Moreover, 100% of the positive feces samples had normal consistency (firm) and all parasitized animals were reared in pens with a concrete floor. A statistical variation was observed in the BCS of parasitized animals compared to non-parasitized ones (p > 0.0253). The results showed that the occurrence of Cryptosporidium in experimental goats located in the municipality of Teresina, State of Piauí, Brazil, was considered low, requiring sanitary management measures to prevent infection in animals and humans. This is the first report of Cryptosporidium infection in goats in the State of Piauí.
Ocorrência de Cryptosporidium em cabras da raça Anglonubiana no município de Teresina, estado do Piauí, Brasil
Keywords: cryptosporidiosis; goats; Ziehl-Neelsen; zoonosis